Bridging identity 'chasms': occupational therapy academics' reflections on the journey towards scholarship. Issue 3 (2nd April 2016) - Fortune, Tracy; Ennals, Priscilla; Bhopti, Anoo; Neilson, Cheryl; Darzins, Susan; Bruce, Christopher
ABSTRACT: The performative context of higher education demands that practice-oriented academics shift their priorities from preparing practitioners for the profession, towards 'productive' scholarship. We present narratives from occupational therapy academics at the end of a year-long journey through an action research project focussed on academic identity and scholarly growth. Our analysis captures subtle and striking shifts in being and becoming, doing and belonging. The findings, re-presented as an adapted Hero ' s Journey, also reveal the powerful impacts on identity and practice that are enabled when academics have the opportunity to create spaces for scholarship that are experienced as caring, collaborative and collegial.